Prognostic value of atrial fibrillation in group of patients with myocardial infarction. Long-term observation results - M. V Soloveva; S. A. Boldueva (Российский кардиологический журнал, 2021)
Purpose. To assess the effect of preexisting atrial fibrillation (AF) on prognosis in patients with type 1 myocardial infarction (MI).Material and methods. These patients were selected from 1660 patients with MI admitted to cardiology department of the NWSMU named after I.I. Mechnikov in 2013-2018. They formed the main group (100 patients). The control group included 200 patients with type 1 MI without AF with the same gender, age. In order to balance groups by prognostically significant factors propensity score matching was carried out. Тhen effect of AF on endpoints was assessed.Results. Patients with type 1 MI and preexisting AF have higher comorbidity, lower ejection fraction. In this group in-hospital pulmonary embolism (PE) (9 % versus 1 % in patients without AF, p=0,0011), minor bleeding (21 % versus 9,5 %, p=0,0057), combined endpoint (stroke + PE + mortality) (19 % versus 10,5 %, p=0,0415) were more common. In the long-term period patients with AF had a higher rate of hospitalizations due to decompensation of chronic heart failure (CHF) (OR=2,47 (95 % CI =1,20–5,08), p=0,0137) and higher incidence of minor bleeding (OR=10,77 (95 % CI =2,36–49,24), p=0,0022). Preexisting AF in patients with type 1 MI (after adjustment for prognostically significant factors) increased the risk of all-cause (OR=5,0 (95 % CI =1,5-17,1), p=0,0072) and cardiovascular mortality (OR=4,1 (95 % CI =1,1-14,9), p=0,0236), increased the risk of CHF III-IV (OR=4,9 (95 % CI =1,2–20,4), p=0,0147), but had no effect on the frequency of ischemic events.Сonclusion. In patients with type 1 MI and pre-existing AF in-hospital and long-term prognosis is worse than in patients without AF. Preexisting AF in these patients is an independent predictor of severe CHF at discharge, cardiovascular and all-cause mortality over follow-up period.